Study of the crystallization kinetics of ferroelectric nanocrystals into TeO2-based glass system - de Oliveira, R. C. [UNESP]; Silva, A. C.A.; Dantas, N. O.; Guerra, J. D.S. (Taylor & Francis, 2018)
Tellurite-based (TeO2) glass systems are known to have relatively high chemical and thermal stability, high transmittance in the infrared region as well as low light dispersion. Parallel to the investigations of the optical properties of the TeO2-based glasses, there is a growing interest in the manufacture of transparent oxides containing specific nanocrystals in the glass-matrix, thus promoting the formation of glass-ceramic materials. These new class of materials are very interesting for new optical-glasses applications. This work aims the investigation of the synthesis process and formation of ferroelectric nanocrystals in tellurite glasses-matrix, obtained by the conventional quenching method.
Keywords: Ferroelectric nanocrystals; glass ceramics; mechanisms of crystallization; TeO2-based glasses